The Role of Digital (Social Media) in Changing Clean and Healthy Living Behavior Among Urban Adolescents in South Minahasa Regency - Wiwin Imelda Opod; Arlin Adam; Andi Alim (Lembaga Pengembangan Kinerja Dosen, 2025)
Social media has become an integral part of adolescents' daily lives and plays a crucial role in shaping their lifestyles, including health-related behaviors. This study aims to analyze the role of social media in encouraging changes in clean and healthy living behavior (PHBS) among urban adolescents in South Minahasa Regency. A quantitative approach with a descriptive design was employed, and data were collected using questionnaires distributed to 100 adolescents residing in the Amurang and Tumpaan areas. The collected data were analyzed descriptively to identify the patterns of information access, the types of platforms used, and the impact of health-related content on adolescents’ behavior. The findings indicate that 78% of respondents admitted to obtaining information about PHBS from social media platforms, with TikTok and Instagram being the most influential. Furthermore, 65% of respondents reported experiencing positive changes in personal hygiene practices, such as regular handwashing and maintaining oral health, as well as improvements in environmental hygiene, including waste management and household cleanliness. Social media health content that is visually engaging, short in duration, and easy to understand was perceived as more effective in influencing adolescents’ daily practices. In addition, peer interaction within social media platforms was found to strengthen motivation and foster a sense of collective responsibility in adopting healthier behaviors. This study highlights that social media serves not only as a source of information but also as a medium of behavioral reinforcement among adolescents. However, the effectiveness of these platforms largely depends on the quality, relevance, and cultural suitability of the health messages delivered. Therefore, the conclusion of this study emphasizes the need for a more structured, engaging, and locally-based digital communication strategy to maximize the impact of social media as a health promotion tool.